Intimate Partner Violence in an Orthodox Jewish Community in the United States: A Qualitative Exploration of Community Members’ Perspectives - Murugan, Vithya (Violence against women, 2023)
This study sought to understand the needs and priorities of the Orthodox Jewish community around intimate partner violence in a medium-sized midwestern city. Twelve Orthodox Jewish rabbis, Rebbetzins, and community members (including survivors) were recruited to participate in in-depth, semistructured interviews. Interviews were analyzed using Dedoose via a mixed content analysis approach. Interviews revealed four themes: (1) Orthodox Gender Norms and Socialization: Risk or Protective Factor? (2) Awareness of DV Services in the Community; (3) Barriers to help-seeking; and (4) Salience of Rabbis and Rebbetzins. Recommendations for culturally congruent programs and practices are discussed.